CONSTRUCTING AN INTEGRATED BUSINESS PLAN FRAMEWORK: A STRATEGIC BLUEPRINT - Shaira Ismail; Nurul Hayani Abd Rahman; Nani Ilyana Shafie; Muhamad Shafri Daie (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
A business plan is crucial to outline business objectives and the strategic approaches to achieve them. A well-constructed business plan framework incorporates several key components that provide a comprehensive and systematic view of the business landscape. Central to this framework is a competitive analysis, which evaluates the market competition, identifies key competitors, and establishes the business’s unique value proposition and competitive edge. The literature review highlights the importance of incorporating various disciplines, such as marketing, finance, accounting, operations, and human resources, into the business plan, subsequently enhancing the entrepreneurs’ ability to address complex business challenges holistically. Key elements of the business plan include a thorough description of products and services, pricing strategy, and development stage. Establishing a clear differentiation from competitors, whether through technological innovations, specialised expertise, or proprietary assets, can strengthen market positioning and potential success. A comprehensive competitor analysis also allows businesses to refine strategies and adapt more effectively to market demands. In conclusion, developing a well-structured and strategic business plan is indispensable as it enables businesses to anticipate challenges, maps the paths to financial stability and growth, and provides a solid foundation for securing investor confidence. Beyond operational optimisation, business plan is a pivotal tool that shapes the future of a business by guiding informed decision-making, facilitating risk management, and aiding in the acquisition of capital.